Studies of UV Spectra of Methylene Blue Dye - Kumar, A.; Sinha, Sushma; Sharan, A.B. (Asian Journal of Chemistry, 2012)
Spectrophotometric studies of methylene blue dye (3,9-bis-dimethyl amino phenazothionium chloride) with solvents like chloroform, water, acetone and amyl alcohol of different polarity have shown the existence, in each case, of a new intense long wave length absorption band in the range of 640-700 nm of the visible region. Such band has been tentatively assigned as charge transfer band due to interaction between Zn ion and phenazothionium ion. The oscillator strength and some spectral characteristics of solute-solvent interaction have also been determined and it has been found that observed red shift of such long wavelength band of methylene blue molecule in solvents in the order of chloroform-water-acetone and amyl alcohol is exactly of the order of their dipole moment values. The oscillator strengths determined seem to be inversely related with the dipole moments.